Assessment of canthal index among the Nepalese and Indian MBBS students of a Medical College in Eastern Nepal - Shah, Diwakar Kumar; Bhakta, Shalini; Khatun, Sanzida; Mahat, Samyog; Jha, Manisha; Sharma, Nitasha (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: The human face is a symbol of artistic expression and identity, with the orbit being a crucial factor in evaluating facial attractiveness. Various orbital measures, such as interpupillary distance, nasal limbus to temporal limbus, inner intercanthal distance, and outer intercanthal distance, are significant in ophthalmology and can help diagnose naso-orbitoethmoid damage, hypertelorism, and traumatic telecanthism. Hence, this study aimed to determine inner and outer canthal distances, mean canthal index values, and compare these values in the Indian and Nepalese MBBS students of Nobel Medical College Teaching Hospital. Methods: A comparative cross-sectional study was conducted among 64 Indian and 128 Nepalese MBBS students aged 18 to 25 years in the Department of Anatomy at Nobel Medical College Teaching Hospital, Biratnagar from April to September 2023. The study used a convenience sample technique and involved measuring the inner canthal distance, outer canthal distance and calculating the canthal index. Results:The overall mean canthal index was 17.93±3.13, the mean outer canthal distance and inner canthal distance were found to be 110.66±12.34 mm and 19.85±4.24 mm respectively. The mean value of the canthal index for Indian and Nepalese students was found to be 18.09±2.99 and 17.85±3.21 respectively. Conclusions: The study found no significant differences in canthal distance or index between Nepalese and Indian students, possibly due to race and geographical habitat pattern similarities.